WHAT CONSIDERATIONS SHOULD THE SCHOOLS OR TEACHERS TAKE INTO ACCOUNT WHEN IMPLEMENTING ENGLISH-INDONESIAN BILINGUAL PROGRAM IN THEIR SCHOOLS? - Sultan Baa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
English-Indonesian bilingual education (BE) program has been implemented in Indonesia for several decades, starting from primary school to tertiary education both by public and private educational institutions. Unfortunately, many stakeholders have questioned about the result of the implementation of the program in Indonesian schools especially in public or government schools. This article presents five strategies that schools or teachers need to be taken into account if they want to achieve successful English-Indonesian bilingual program, namely: (1) sufficient bilingual teacher supply; (2) ongoing teacher professional development; (3) communicative classroom strategies; (4) English in the school context; and (5) collaboration between language and content teachers